Beneficial Role of Reduced Graphene Oxide for Electron Extraction in Highly Efficient Perovskite Solar Cells. Issue 21 (22nd September 2016) - Cho, Kyung Taek; Grancini, Giulia; Lee, Yonghui; Konios, Dimitrios; Paek, Sanghyun; Kymakis, Emmanuel; Nazeeruddin, Mohammad Khaja
Abstract: In this work we systematically investigated the role of reduced graphene oxide (rGO) in hybrid perovskite solar cells (PSCs). By mixing rGO within the mesoporous TiO2 (m‐TiO2 ) matrix, highly efficient solar cells with power conversion efficiency values up to 19.54 % were realized. In addition, the boosted beneficial role of rGO with and without Li‐treated m‐TiO2 is highlighted, improving transport and injection of photoexcited electrons. This combined system may pave the way for further development and optimization of electron transport and collection in high efficiency PSCs. Abstract : rGO for efficiency ! The effect of incorporating reduced graphene oxide (rGO) within the electron‐transport, active, and hole‐transport layers of a perovskite solar cell is investigated. Incorporation of rGO into the mesoporous TiO2 matrix results in highly efficient solar cells with power conversion efficiency of up to 19.54 %.